2019
DOI: 10.1186/s12967-019-1860-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and development of machine learning tools in the prediction of chronic kidney disease progression

Abstract: Background Urinary protein quantification is critical for assessing the severity of chronic kidney disease (CKD). However, the current procedure for determining the severity of CKD is completed through evaluating 24-h urinary protein, which is inconvenient during follow-up. Objective To quickly predict the severity of CKD using more easily available demographic and blood biochemical features during follow-up, we developed and compared several predictive models using sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(98 citation statements)
references
References 41 publications
(35 reference statements)
6
92
0
Order By: Relevance
“…We evaluated the predictive performance of these 6 models for COPD and found that the XGboost model presented the best AU-ROC and AU-PRC values in both the training and test sets in all features. The XGboost algorithm is a highly effective and widely used machine learning method that can build complex models and make accurate decisions when given adequate data [65]. We used the XGboost model to predict feature importance, and the results indicated that the AQCI was the most important factor, while SNPs were less important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the predictive performance of these 6 models for COPD and found that the XGboost model presented the best AU-ROC and AU-PRC values in both the training and test sets in all features. The XGboost algorithm is a highly effective and widely used machine learning method that can build complex models and make accurate decisions when given adequate data [65]. We used the XGboost model to predict feature importance, and the results indicated that the AQCI was the most important factor, while SNPs were less important.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the linear LR model [64] and SVM model have been widely adopted in many clinical applications, such as for CKD disease prediction [65]. The DT model [66] is based on a radial basis function neural network and support vector machine coupled with firefly algorithm techniques; the XGboost and MLP models have also been used in clinical research [65,67]. KNN was chosen due to its simplicity and ability to perform multiclass classification, and this algorithm could run with default parameters [68].…”
Section: Model Construction In the Training Setmentioning
confidence: 99%
“…Their study obtained 85.3% accuracy to detect CKD. In 2019, Jing Xiao conducted a study to detect various stages of CKD [8]. This study used the logistic regression machine learning technique to train the model and used online tool for prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Their comparative study revealed that Radial Basis Function provides the best accuracy rate with 85.3 percentage. Jing Xiao [8] established nine models and compared their performance to predict the CKD stages according to its severity. Predictive models include ridge regression, lasso regression, logistic regression, Elastic Net, XG Boost, neural network, k-nearest neighbor, random forest and support vector machine.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have introduced predictive models for diseases such as diabetic retinopathy, skin cancer, lung disease, heart failure, chronic kidney disease, and so on using machine learning techniques [14][15][16][17][18][19][20]. These studies that use deep learning techniques to make major advances in solving problems have resisted the best attempts of the artificial intelligence community in many cases [21].…”
Section: Introductionmentioning
confidence: 99%